Marx, Anderson and the Critique of Indian Political Economy and the Caste System. Issue 2 (December 2019) - Sampath, Rajesh
Abstract: This article will deconstruct the assumptions of the famous British Western Marxist, Anderson (2012), and his recent critique of the Indian political economy in his controversial The Indian Ideology . Anderson's work is a blistering critique of the origins of the post-British colonial Indian political-economy, society and culture. The paper examines different critical responses to Anderson's work by Indian intellectuals in light of our re-interpretation of Marx and Engel's classic, The German Ideology . Our aim is to critically appropriate the salience of Ambedkar's ideas today in treating contemporary modalities of social exclusion, the continued practice of caste discrimination and political and constitutional responses to caste inequality. The paper argues for the development of new philosophical tools beyond the twentieth century Western Marxist frameworks, which informs the work of current thinkers like Anderson, to extend in new directions Ambedkar's initial impulses in the South Asian critique of caste.